MEMORIES OF ANGELS AND THE CHANGING LANDSCHAPE SACRED:: Folklore, Ecology, and Tourism at Lake Rowobayu in the “Desa Penari” - Nasution (Universitas Negeri Surabaya, 2025)
This study research transformation folklore, ecology sacred, and tourism culture at Lake Rowobayu, Banyuwangi, with attention specifically on the figure Badarawuhi, water symbolism, and impact tourism triggered by films after KKN in Penari Village. Use approach qualitative based on observation field, interview in-depth and analysis narrative thematic, study This explore How folklore in a way historical functioning as governance system​ informal environment rooted in cosmology local. Findings show that although folklore Once arrange behavior ecological through taboo and fear, its effectiveness has decrease Because commodification, media exposure, and governance weak structural, a​ conceptualized conditions​ as failure folklore. Although thus, folklore still relevant among​ segment society that maintains trust traditional Hindu- influenced culture, where ecology sacred Keep going support attitude-oriented conservation. This study also found that film-fuelled tourism has speed up desacralization Rowobayu, change it become destination recreation and improve pressure ecological research​ This contribute to the study folklore and tourism with integrate ecology sacred, ecology politics, and media representation, with argue that tourist culture sustainable need planting return folklore in system living trust and a strong governance framework​​ For switch from respect symbolic going to protection ecological material.